The quantum conductance of ballistic microconstrictions in metals with an open Fermi surface: Электpонные свойства металлов и сплавов - Namiranian, A.; Kolesnichenko, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
It is shown that the conductance G of a quantum microconstriction in a metal with an open Fermi surface undergoes jumps e2/h of the opposite sign as a function of the contact diameter. The negative jumps are a result of the limitation of the energy of the electron motion along the direction in which the Fermi surface is open. The point contact spectrum dG/dV of such a constriction has additional peaks at the bias eV where the maximum energy emax of the quantum subband is equal to the energies eF ╠ eV/2 (eF is the Fermi energy).